Oral and cutaneous manifestations of Erythema Multiforme related to the use of oxcarbazepine in a patient with epilepsy: A case report (Research, Society and Development, 2026)
Oxcarbazepine is an anticonvulsant widely used in the treatment of epilepsy; however, it may be associated with mucocutaneous adverse reactions, such as erythema multiforme. This study aims to report a case of erythema multiforme major with oral and cutaneous manifestations associated with oxcarbazepine use in a young patient with epilepsy and neuropsychomotor impairment. A 25-year-old female patient, under continuous oxcarbazepine therapy for more than ten years, presented recurrent episodes of vesiculobullous and ulcerative lesions in the oral cavity, preceding cutaneous lesions on the palmar surface of the hands. Extensive laboratory investigations revealed no significant abnormalities. Lesion remission was observed after discontinuation of oxcarbazepine, with recurrence following drug reintroduction, establishing a causal relationship. Drug replacement combined with systemic and topical corticosteroid therapy resulted in complete lesion resolution. The diagnosis of erythema multiforme was based on clinical features and disease progression. This case highlights the importance of recognizing oral manifestations as early indicators of adverse drug reactions and emphasizes the role of dental professionals in multidisciplinary patient care.